Foreign experience of combating corruption - Kapsalyamov, K.Zh.; Kapsalyamova, S.S. (Bulletin of the Karaganda University “Law Series”, 2018)
Today our country is going through a difficult period in its history in the way of a radical reconstruction of the political and economic system. Evidence of this are achieved in the present concrete results of economic reform: practical market mechanism for the regulation of production, eliminated pre-existing shortage of the commodity-denini mass, optimization of economic-legal regulation in foreign trade. However, there are still a number of negative phenomena and processes in the formation of the market economy, which unfortunately has a negative impact on the country's economy — corruption and shadow economic activities. We know many reasons of corruption crime in the economic sphere. There are many examples of corruption. Very often, according to analytical information, it has negative manifestations in the sphere of use of public resources to improve their material well-being representatives of the government. In the implementation of corruptive criminal offences with the use of official capacity to call officials with contacts in the customs sphere, as well as law enforcement officers. Presented in this paper the experience of foreign States in the sphere of regulation of responsibility for crimes committed by civil servants and persons equated to them, as well as the related malfeasance are very diverse, often contradictory and changeable, but in any case, highly instructive. However, it is necessary to pay attention that the foreign rules can provide many benefits in the domestic rulemaking on razresheny of the problems regarding fighting corruption offences.